Aquinas on Virtue A Causal Reading - Austin, SJ, Nicholas (Moral Traditions series, 2018)
Thomas Aquinas (1225-1274), an Italian Dominican friar and Catholic priest, is one of the most influential theologians in the Christian tradition. Scholarship on Aquinas is flourishing, with studies of natural law theory, action theory, the morality of the passions, feminism, political theory, etc. Yet despite the contemporary renewal of virtue ethics, to date no full-length treatment of Aquinas' theory of virtue exists. Aquinas on Virtues offers a new and comprehensive interpretation of how Aquinas uses the four causes--formal, material, final, and efficient--to understand virtue in general, and how these causes underlie his treatment of specific virtues that make up the bulk of his ethics. In the final part of the book Austin applies the causal approach to four contested issues in contemporary virtue theory: practical wisdom; virtue and the passions; the teleology (or ultimate end) of virtue; and infused moral virtues, exploring the relation between grace and virtue.